The hangover - Todd Phillips; Warner Bros. Pictures; Christophe Beck; e irector of photography9; Jon Lucas; e; e; Reliance Big Entertainment (Mumbai, India) (Mumbai : Reliance Big Entertainment, 2009)
Angelenos Doug Billings and Tracy Garner are about to get married. Two days before the wedding, the four men in the wedding party - Doug, Doug's two best buddies Phil Wenneck and Stu Price, and Tracy's brother Alan Garner - hop into Tracy's father's beloved Mercedes convertible for a 24-hour stag party to Las Vegas. Phil, a married high school teacher, has the same maturity level as his students when he's with his pals. Stu, a dentist, is worried about everything, especially what his controlling girlfriend Melissa thinks. Because she disapproves of traditional male bonding rituals, Stu has to lie to her about the stag, he telling her that they are going on a wine tasting tour in the Napa Valley. Regardless, he intends on eventually marrying her, against the advice and wishes of his friends. And Alan seems to be unaware of what are considered the social graces of the western world...
Copyright notice on container: Moser baer
Originally released theatrically in 1967.
Summary taken from IMDB.com.
Zach Galifianakis, Bradley Cooper and Justin Bartha
Dual Layer format, Colour, Widescreen 2.40:1, 5.1 Dolby digital
English
Keywords: Commedy -- Drama; Crime -- Drama